2023
DOI: 10.3390/app132212480
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Test of Coarse-Grained Soils Reinforced with One Layer of Geogrid

Mindaugas Zakarka,
Šarūnas Skuodis,
Neringa Dirgėlienė

Abstract: Geosynthetics play a pivotal role in modern infrastructure projects, with geogrids serving as a common choice for enhancing bearing capacity and reducing soil settlement in road construction. This study investigates the influence of density and uniformity coefficients on geogrid-reinforced sandy and gravelly soils through a series of consolidated drained triaxial tests. The research covers six distinct soil types from Lithuania, each characterized by particle size distribution analysis and classified using var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Scholars employing this method have documented significant findings regarding the mechanical properties of reinforced soils. Zakarka et al conducted studies on geogrid-reinforced coarse-grained soils through triaxial testing and observed that increasing perimeter pressure reduces the effectiveness of geogrid reinforcement [15,16]. Xiaobin et al investigated the shear performance of such soils reinforced with geogrids using large-scale triaxial tests, revealing that geogrids significantly enhance viscous cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars employing this method have documented significant findings regarding the mechanical properties of reinforced soils. Zakarka et al conducted studies on geogrid-reinforced coarse-grained soils through triaxial testing and observed that increasing perimeter pressure reduces the effectiveness of geogrid reinforcement [15,16]. Xiaobin et al investigated the shear performance of such soils reinforced with geogrids using large-scale triaxial tests, revealing that geogrids significantly enhance viscous cohesion.…”
Section: Introductionmentioning
confidence: 99%